Risk and the law - Woodman, Gordon R.; Klippel, Diethelm (London ; New York : Routledge-Cavendish, 2009)
This volume brings together international experts to examine the implications in practice of the modern concept of risk in particular legal fields. The papers question how the law can accommodate, manage, and reduce the extent of risk, a matter of pressing importance for the development of law in all jurisdictions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Risk; Liability (Law); Juristic acts; Risk assessment; Electronic books; Electronic books